Prevalence and Species Diversity of Eimeria in the Poultry of Chhattisgarh Plains - Shandey, Mohanlal; Pal, Susanta; Bisen, Savita; Raj, Lourde; Ram Baghel, Kashee (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The present study was undertaken to determine the prevalence of coccidia parasites in poultry across both organized and unorganized farms in four districts, namely Bilaspur, Durg, Korba and Rajnandgaon, located in the plain region of Chhattisgarh. The overall prevalence of poultry coccidiosis was found to be 17.5% (42/240), with organized farms showing an infection rate of 17.2% (31/180), while unorganized farms exhibited a slightly higher rate of 18.3% (11/60). The highest prevalence (40%) was recorded in unorganized farms of the Korba district. Morphometric analysis of the oocysts revealed the presence of mixed Eimeria infections in all sampled farms, with 3 to 6 species identified per location. The most prevalent species across the region were E. acervulina (93.75%), E. maxima (87.5%), E. mitis (87.5%) and E. tenella (81.25%), followed by E. necatrix (25.0%), E. praecox (12.5%) and E. brunetti (12.5%). These findings highlight the widespread nature of mixed Eimeria infections in both organized and unorganized poultry systems. Regular monitoring and region-specific control strategies are essential to minimize production losses due to coccidiosis in Chhattisgarh.